FACIAL EXPRESSIONS AND GESTURES OF BODY LANGUAGE ANALYSIS OF THE MALE MAIN CHARACTER JACK MCCALL IN A THOUSAND WORDS FILM 2012 - RIZKIYA WINDAYANTI, RAHMA (Language Horizon: Journal of Language Studies, 2014)
FACIAL EXPRESSIONS AND GESTURES OF BODY LANGUAGE ANALYSIS OF THE MALE MAIN CHARACTER JACK MCCALL IN A THOUSAND WORDS FILM 2012 Rahma Rizkiya Windayanti English Literature, Languages and Arts Falculty, State University of Surabaya rahmarizkiya@gmail.com Drs. Suwono, Ph.D. English Literature, Languages and Arts Faculty, State University of Surabaya nanosuwono@gmail.com Abstrak Studi ini mengacu pada studi komunikasi nonverbal, khususnya studi bahasa tubuh. Studi ini fokus pada analisis ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh oleh pemeran laki-laki utama Jack McCall di film A Thousand Words. Lagi pula, masyarakat mengekspresikan ekspresi wajah dan gerak isyarat tubuh guna mendukung komunikasi secara verbal. Melalui film A Thousand Words, studi ini bertujuan untuk mengetahui makna dibalik ekspresi wajah dan gerak isyarat tubuh oleh pemeran laki-laki utama Jack McCall sebagai penggambaran dari ekspresi wajah dan gerak isyarat tubuh yang diekspresikan oleh masyarakat di seluruh dunia. Ada tiga tujuan dalam analysis studi ini. Yang pertama, studi ini bertujuan untuk mengidentifikasi macam-macam ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh yang diekspresikan oleh pemeran laki-laki utama Jack McCall. Yang kedua, studi ini bertujuan untuk mengidentifikasi makna dari ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh yang diekspresikan oleh pemeran laki-laki utama Jack McCall. Dan yang terakhir, studi ini bertujuan untuk mendeskripsikan bagaimana ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh bekerja dalam interaksi antara pemeran laki-laki utama Jack McCall dan para pemeran lainnya. Beberapa teori dari sumber yang berbeda-beda digunakan untuk membuat studi ini lebih akurat. Teori-teori tersebut digunakan untuk mendukung proses analisis studi ini. Kualitatif deskriptif adalah sebuah metode yang digunakan untuk menjawab permasalahan-permasalahan dalam studi ini. Datanya adalah sebuah film yang berjudul A Thousand Words. Film ini dipublikasikan pada tahun 2012. Data ini dideskripsikan dalam bentuk gambar-gambar dan kata-kata. Berdasarkan dari studi ini, ditemukannya macam-macam ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh yang diekspresikan oleh pemeran laki-laki utama Jack McCall, seperti simple smile, upper smile, broad smile, eyes raise, eyes stare, eyes weep, forefinger point, forefinger raise, hand shake, arms behind, the nose touch, the mouth cover, chin stroking, boredom gesture, hands clenched together, legs cross knee-knee, and legs cross ankle-knee. Juga ditemukannya makna dari ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh untuk mengungkapkan perasaan jujur oleh pemeran laki-laki utama Jack McCall. Dan yang terakhir, ditemukannya bagaimana ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh bekerja dengan baik atau tidak dalam berinteraksi antara pemeran laki-laki utama Jack McCall dan para pemeran lainnya. Untuk memahami permasalahan-permasalahan ini, harus dilihatnya penggunaan ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh melalui konteks sosial, seperti subyek, waktu, tempat, topik pembicaraan, atau situasi. Di akhir analysis, studi ini diharapkan memperluas pengetahuan dan pandangan terhadap fenomena ekspresi wajah dan gerak isyarat tubuh dari bahasa tubuh yang digunakan untuk mengekspresikan perasaan yang sebenarnya. Kata Kunci: Komunikasi Nonverbal, Bahasa Tubuh, Ekspresi Wajah, Gerak Isyarat Tubuh, dan konteks. Abstract This study refers to the nonverbal communication study, especially body language study. This study focuses on the analyzing of facial expressions and gestures of body language of the male main character Jack McCall in A Thousand Words film. Moreover, people express facial expressions and gestures in order to support communicating verbally. Through A Thousand Words film, this study is used to know the meaning behind facial expressions and gestures of the male main character Jack McCall as a representation of them which are expressed by people around the world. There are three purposes of analyzing this study. First, it is used to identify the kinds of facial expressions and gestures of body language which are expressed by the male main character Jack McCall. Second, it is used to identify the meaning of facial expressions and gestures of body language which are expressed by the male main character Jack McCall. And the last, it is used to describe how facial expressions and gestures of body language work in the interaction between the male main character Jack McCall and other characters. Several theories from different sources are used to make this study more valid. These several theories are used to support the process of analyzing this study. Descriptive qualitative is a method that is used to answer the problems in this study. The data is a film entitled A Thousand Words. This film was published in 2012. This data is described in the form of images and words. From this study, it can be found the kinds of facial expressions and gestures of body language which are expressed by the male main character Jack McCall, such as simple smile, upper smile, broad smile, eyes raise, eyes stare, eyes weep, forefinger point, forefinger raise, hand shake, arms behind, the nose touch, the mouth cover, chin stroking, boredom gesture, hands clenched together, legs cross knee-knee, and legs cross ankle-knee. It can also be found the meaning of facial expressions and gestures of body language to reveal the true feeling of the male main character Jack McCall. And the last, it can be found how facial expressions and gestures of body language successfully work or not in the interaction between the male main character Jack McCall and other characters. To understand these problems, it must be looked at the using of facial expressions and gestures of body language from the social context, such as subject, time, place, topic of conversation, or situation. In the end, this study is hoped enlarge the knowledge and our view on the phenomenon of facial expressions and gestures of body language which are used to express the true feeling. Key Words: Nonverbal Communication, Body Language, Facial Expressions, Gestures, and Context. BACKGROUND OF THE STUDY Communication is important for everybody because they need to communicate to one another. According to Everett M. Rogers and D. Lawrence Kincaid (in Cangara, 2009: 20), komunikasi adalah suatu proses dimana dua orang atau lebih membentuk atau melakukan pertukaran informasi antara satu sama lain yang pada gilirannya terjadi saling pengertian yang mendalam (Communication is a process of two people or more which is formatting or exchanging information one another, it will occur a deep mutual understanding). The process of communication is divided by two, verbal communication is a medium for communication that entails talking using the spoken word, such as talking face-to-face, on a telephone, or as a speech, while nonverbal communication is a medium for communication that entails using cues via body language to convey message content.(1) Communication verbally means speaking. Everybody will speak when communicating to one another. However, communicating verbally is not the only way to communicate. Henry H. Calero states that humans have capability of receiving information besides what is written or spoken (2005: 1). So, humans have capability for communicating using their body movements as a symbol or a signal while speaking. Body language is a universal language which is expressed by people around the world. Nonverbal communication has been used as a primary communication tool since thousands years ago. Henry H. Calero explains that for thousands of years, mankind has used wordless messages to communicate, thoughts, attitudes, ideas, and emotions, by using gesture, posture, facial expressions, sounds, and symbols (2005: 2). In the past, people had not been familiar with writing and language yet, so people communicated using body movements to one another. Nowadays, people still communicate nonverbally while speaking. A person who speaks will express some expressions from his body movements consciously and unconsciously. Understanding about body language in nonverbal communication cannot be separated from the context. By Teun A. van Dijk, the term “context” is used to the “social situation” of language in general (2009: 2). The body language occurs in the conversation for expressing the spoken words. So, to understand about the body language, it is required to understand about the context. The context refers to the social situation is about subject, place, time, situation, or topic of conversation. This context is used to understand the expression of body language correctly. The scientific name of body language is kinesics. According to Marcel Danesi, body language is the general term used to indicate communication by means of gestures, postures, and other witting and unwitting body signals and signs (2004: 53). To recognize the body movements, it can be seen from the gestures and facial expressions. According to David McNeill, gestures I mean are everyday occurrences – spontaneous, unwitting, and regular accompaniments of speech that we see in our moving finger, hands, and arms (2005: 3). Another sign of body language is facial expression. Facial expressions are the expression through the signal of smile and eyes. Facial expressions are expressed consciously and unconsciously. According to Henry H. Calero, a research has revealed that messages are conveyed between individuals 55 percent from the body, 38 percent from the voice – inflection, intonation, volume – and 7 percent from the words (2005: 5). According to the research, body language gives bigger contribution than the intonation of voices or words. It can be concluded that a person feels more satisfy if he expresses his spoken or feeling by using the body movements. Based on these backgrounds, previous study is needed for helping to analyze this study. This previous study entitled Gestures Used In Oprah TV Show. This study focuses on the gestures of Oprah Winfrey in Oprah TV Show. Strengthens of this study is Oprah Winfrey has her own style when she is interacting with guest star and audiences. However, the weakness of this study is smile and eyes signals are parts of head or face gesture. Theoretically, gesture is a signal of body movements. So, smile and eyes signal should be categorized as facial expressions. This study will analyze facial expressions and gestures of body language which are expressed by the male main character Jack McCall in A Thousand Words film. This film was directed by Brian Robbins and published in 2012. The male main character Jack McCall was played by Eddie Murphy. A Thousand Words film tells about the story of the male main character Jack McCall who is cursed by a magic tree that loses a leaf with every word he speaks. This film is interesting to be analyzed because the male main character Jack McCall expresses facial expressions and gestures of body language when he is communicating with the other characters. By these problems, the purpose of this study is used to know the kinds of facial expressions and gestures of body language that cover-up the conversation between Jack McCall and other characters. To know about this problem, it is necessary to know the kinds of facial expressions and gestures which are expressed by the male main character Jack McCall, the meaning of facial expressions and gestures of body language which are expressed by the male main character Jack McCall, and how facial expressions and gestures of body language work in the interaction between Jack McCall and other characters in A Thousand Words film. RESEARCH METHOD The data analyzed based on the nonverbal communication theory, especially in facial expressions and gestures of body language. According to Dornyei (2007: 126), qualitative research on the other hand, focuses on describing, understanding, and clarifying a human experience. In this study, it was analyzed human experience such as human behavior through facial expressions and gestures of body language and human’s problem based on the context. The data that was analyzed was the male main character Jack McCall in A Thousand Words film published in 2012. Based on Miles and Huberman, three aspects of analysis: data reduction, data display, and the drawing of conclusions. a Data Reduction: Selecting relevant or irrelevant data and then, classifying the data based on the kinds of facial expressions and gestures. By classifying the data, it has been found 17 kinds of facial expressions and gestures of body language involved 6 facial expressions and 11 gestures. b Data Display: The data which was selected and classified was inserted into a table. These data involved picture of the male main character Jack McCall, time, characters, setting, plot, action, and indication. c The Drawing of Conclusions: identifying the kinds and the meaning of facial expressions and gestures of body language which were expressed by the male main character Jack McCall. And then, describing how those facial expressions and gestures of body language work in the interaction between the male main character Jack McCall and other characters The researcher concluded the whole analyses of facial expressions and gestures of body language which were used by the male main character Jack McCall in A Thousand Words film 2012 based on nonverbal communication theory. DISCUSSION Jack McCall expresses facial expressions and gestures of body language in A Thousand Words film. There are 17 kinds of facial expressions and gestures of body language which are involved 6 facial expressions and 11 gestures. These 6 facial expressions which are expressed by the male main character Jack McCall consist of simple smile, upper smile, broad smile, eyes raise, eyes stare, and eyes weep. While, 11 gestures which are expressed by the male main character Jack McCall consist of forefinger point, forefinger raise, hand shake, arms behind, the nose touch, the mouth cover, chin stroking, boredom gesture, hands clenched together, legs cross knee-knee, legs cross ankle-knee. Those kinds of facial expressions and gestures of body language which are expressed by the male main character Jack McCall are a representation of facial expressions and gestures of body language which are expressed by people around the world. On the other words, those kinds of facial expressions and gestures of body language which are expressed by the male main character Jack McCall is a universal body language. According to the data of facial expressions, there are three example of simple smile which is found in the male main character Jack McCall. Upper smile consists of two examples. Broad smile consists of two examples. Eyes raise consists of one example. Eyes stare consists of three examples. And Eyes weep consists of one example. While, according to the data of gestures, there are four examples of forefinger point. Forefinger raise consists of one example, hand shake consist of three examples, arms behind consists of one example, the nose touch consists of one example, the mouth cover consists of one example, chin stroking consist of one example, boredom gesture consists of one example, hands clenched together has one example of, legs cross knee-knee consists of one example, and legs cross ankle-knee consists of one example. Classifying those kinds of facial expressions and gestures of body language which are expressed by the male main character shows the characteristic, example, function, and background of the facial expressions and gestures of body language in general. Those kinds of facial expressions and gestures of body language which are expressed by the male main character Jack McCall have different meaning based on the context. For example: the eyes raise which are expressed by the male main Jack McCall means that he is very angry and shock. According to the data, Jack McCall gets a report from Aaron (Jack’s secretary) of Dr. Sinja’s book are accepted by Aaron. Jack McCall wants to publish Dr. Sinja’s book. But, he gets shock when Aaron said the book only has five pages long. Eyes raise itself have two meanings, first meaning means exasperation or very anger and the second meaning means that a person who is surrender to God. By that example, Jack McCall’s eyes raise means he is very angry. Another example: hand shake is a natural habit which often occurs when two people or more are meeting at the first time. However, hand shake is used to bind a contract. Jack McCall and Dr. Sinja are shaking their right hands together when they are dealing a contract. Dr. Sinja agrees to Jack McCall’s offer. Jack McCall gives an offer to publish Dr. Sinja’s book. Then Dr. Sinja agrees to publish his book. Hand shake is about the dealing a contract. It means that both of them agree to make cooperation. The context which is used to analyze the meaning refers to the social situation, such as setting, plot, conversation, situation, and past experience. The past experience refers to the Jack McCall’s problem. Jack McCall gets a curse by a magic tree that loses a leaf with every word he speaks. The analysis of the meaning of facial expressions and gestures of body language show the true feeling. However, facial expressions and gestures of body language show honesty. Everybody can be lying when talking, but it is difficult to hide the true feeling from the body signals. Facial expressions and gestures of body language are expressed conscious and unconsciously. Additionally, facial expressions and gestures of body language are expressed to support the spoken words. Facial expressions and gestures of body language which are expressed by the male main character Jack McCall give positive and negative impressions to the interlocutor. These facial expressions and gestures of body language which are expressed by the male main character Jack McCall are polite or impolite behavior so the interlocutor is able to accept or not. For example, a smile is a signal of happiness. Jack McCall expresses upper smile when he is introducing to some clients. This upper smile shows a signal of respecting and welcome. Jack McCall gives an appreciation by showing his smiling to someone at the first meeting. This facial expression shows a positive impression to the other character or the interlocutor. The interlocutor does not get insulted by the Jack McCall’s facial expressions. And this facial expression shows polite behavior to the interlocutor. Moreover, a forefinger point is a signal of pointing a direction to a person or something. For example: Forefinger point occurs in the conversation between Jack McCall and a valet. A Valet is asking to Jack McCall about his manuscript, but Jack McCall feels disturbed by the valet’s question. So, Jack McCall answers valet’s questions by expressing forefinger point. Jack McCall’s answer is insulted a valet. So, the forefinger point is used to beat this valet’s in order to not disturb Jack McCall again. Additionally, Jack McCall also expresses his forefinger point to this valet for commanding. He gives a command to this valet to park his car. This valet who feels disappoint does not say anything to Jack McCall. These examples of facial expressions show negative impressions to the other character or the interlocutor. The interlocutor gets insulted by the Jack McCall’s gestures. And this gesture shows polite behavior to the interlocutor. Furthermore, Jack McCall does not speak because of a problem. Jack McCall gets a curse by a magic tree that loses a leaf with every word he speaks. So, Jack McCall can only express his feeling through the facial expressions and gestures of body language. However, facial expressions and gestures of body language which are expressed by the male main character Jack McCall without any spoken words are difficulty understood by other characters or the interlocutors. In this research, it can be found that a lot of misunderstanding between the male main character Jack McCall and other characters. For example: the conversation between Jack McCall and Shrink. The conversation between Jack McCall and Shrink shows that Jack McCall and Shrink do not get any problem of the conversation. Jack McCall who are talkative are talking too much to Shrink. And in this scene, Jack McCall who is sitting by legs cross knee-knee position is wanted to get more attention from Shrink. While, the conversation between Jack McCall and Shrink shows that Jack McCall and Shrink get a problem of the conversation. Jack McCall keeps so silent, so he does not talk anything. Jack McCall does eye contact to Shrink but Shrink feels confused with the Jack McCall behavior in this scene. Therefore, Shrink gets a misunderstanding with the Jack McCall’s behavior. Moreover, to understand those facial expressions and gestures, a person needs to understand the social context which is supporting those behaviors. Based on this research, understanding about social context is able to be done by looking at the conversation, plot, condition, and past experience (problem). In A Thousand Words film, Jack McCall gets a big problem with his speaking. Jack McCall cannot speak because of a magic tree that loses a leaf with every word he speaks. CONCLUSION The male main character Jack McCall expresses facial expressions and gestures when he is communicating with other characters. There are 17 kinds of facial expressions and gestures of body language which involves 6 facial expressions (simple smile, upper smile, broad smile, eyes raise, eyes stare, and eyes weep) and 11 gestures (forefinger point, forefinger raise, hand shake, arms behind, the nose touch, the mouth cover, chin stroking, boredom gesture, hands clenched together, legs cross knee-knee, and legs cross ankle-knee). Facial expressions and gestures of body language which are expressed by the male main character Jack McCall have different meaning based on the context. The meaning of facial expressions and gestures of body language which are expressed by the male main character Jack McCall is identified based on the conversation, situation, the topic of conversation, and the past experience (Jack McCall’s problem). Furthermore, Jack McCall’s problem causes the misunderstanding between him and other characters. Jack McCall does not speak to everybody. Because of this situation, Jack McCall only expresses his feeling through his body signals such facial expressions and gestures. This body signals cannot deliver well Jack McCall’s true feeling to the interlocutor or other characters. This situation causes misunderstanding between Jack McCall and other characters. Facial expressions and gestures of body language which are expressed by the male main character Jack McCall show the positive impressions and negative impression to the interlocutor. It means that these facial expressions and gestures of body language which are expressed by the male main character Jack McCall are insulting the other characters. SUGGESTION Finally, this journal is admitted still far from being perfect. This study only focuses on facial expressions and gestures of body language. Moreover, there is a lot of study of nonverbal communication, especially body language which is not discussed in this study. Hopefully, this study about nonverbal communication is able to be more learned for the next study. This study is hoped enrich the knowledge and the reader’s view on the phenomenon of facial expressions and gestures of body language which are expressed by people around the world. GRATITUTION Alhamdulillah, I say great gratitude to Allah SWT for blessing me for finishing this journal. And great thank you for Mr. Drs. Suwono, Ph.D as my advisor for the attention and advice for finishing this journal. And I do not forget to say thank you very much for my parents who loving, caring, being patient, and giving some advices for finishing this journal. REFERENCES Ahmadi, Abu. 1990. Psikologi Sosial. Semarang Calero, Henry H. 2005. The Power of Nonverbal Communication. Los Angeles: Silver Lake Publishing Cangara, Hafied. 2008. Pengantar Ilmu Komunikasi. Jakarta: PT. Raja Grafindo Persada Danesi, Marcel. 2004. Messages, Signs and Meanings. Toronto, Canadian: Scholars’ Press Inc. Dijk, Teun A. Van. 2009. Society and Discourse. UK: Cambridge University Press. Dornyei Zoltan, 2007. Research Methods in Applied Linguistics. New York: Oxford Univeristy Press Fast, Julius. 1982. Body Language. London: Pan Books Ltd Holmes, Janet. 1997. An Introduction to Linguistic. London: Longman Group UK James, Judi. 2009. The Body Language Rules. England: Sourcebooks, Inc. Jensen, Klaus Bruhn, and Nicholas W. 2002: Editing Edition: A Handbook of Qualitative Methodologies for Mass Communication Research. Tylor & Francis e-Library Kurnia, Oktaviani. 2009. Gestures Used In Oprah TV Show. Surabaya: State University of Surabaya Krauss, Robert M. 2002. Journal: The Psychology of Verbal Communication. Columbia University McNeill, David. 2005. Gesture and Thought. Chicago: The University of Chicago Press Morris, Desmond. 1994. Body Talk. Oxford Nierenberg, Gerard I. and Calero, Henry H. 2001. How to Read a Person Like a Book. Barnes and Nobel Digital Pease, Allan and Pease, Barbara. 2004. The Definitive Book of Body Language. Australia: Pease International Pease, Allan. 1988. Body Language. Australia: Canel Publishing Company Salzmann, Zdenek. 2004. Language, Culture, and Society. USA: Westview Press Sharma, Vinay Mohan. 2011. Body Language. V&S Publishes 1)http://www.toolingu.com/definition-950120-92942-nonverbal-communication.html